Correction: The conversion of a high concentration of lignin to cyclic alkanes by introducing Pt/HAP into a Ni/ASA catalyst. Issue 11 (20th May 2020) - Qin, Shufang; Li, Bolong; Luo, Zhicheng; Zhao, Chen
Abstract : Correction for 'The conversion of a high concentration of lignin to cyclic alkanes by introducing Pt/HAP into a Ni/ASA catalyst' by Shufang Qin et al., Green Chem., 2020, 22, 2901–2908, DOI: ; 10.1039/D0GC00243G .